Determining vulnerable households and food groups sensitive to price and income increase from the perspective of food security: Evidence from Iran - Banaie, Elahe; Mojaverian, Seyed Mojtaba; Mirzaei, Abbas (Frontiers in Sustainable Food Systems, 2023)
Concerns about household food security of developing countries has been greatly intensified with rising food prices derives from various causes, such as market failure, climate change, political instability, the presence of poor financial institutions, and emerging challenges. It is very important, the development and evaluation of required policy responses such as income compensation policy to cope with foodstuff price increases. It is necessary to pay attention to different household groups regarding income, occupation, and urban/rural conditions in order to evaluate the effects of shocks and policies according to the different responses of households. This paper employes a multimarket equilibrium simulation model and evaluates the effect of price hikes with/without households’ nominal income compensation policy on the calorie intake of different household groups. To this end, Iranian households that have suffered from severe food inflation and their nominal income compensation policy has always been the focus of government officials were investigated. First, we noticed that poor rural households with government occupations bear the brunt of ensuing the price hike of foodstuffs. Second, we found that households food security is highly reliant on the price of livestock products compared to other foodstuffs. Finally, we concluded that income compensation policy plays the role of a threat to food security for some households and a driver for others. Therefore, based on the different responses of households to foodstuff price and income shocks, we recommended the design of more precise interventions in the market of foodstuff in a more targeted and efficient manner.